2015
DOI: 10.1177/1354067x15570486
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for a planned migration through ethnic identity talk

Abstract: Previous discursive research on ethnic identity has suggested the complex and multifaceted nature of accomplishing membership in an ethnic group. In this paper, we explore how ethnic identity claims may be used as a resource in accounting for behavior seen as open to the group, namely a planned migration to one's ancestral homeland. A discursive psychological approach is used to analyze focus group data with potential ethnic return migrants, specifically, adults with Finnish roots who intend to migrate to Finl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In all accounts of discrimination presented in this subsection, speakers make relevant their own Finnishness in response to being excluded from Finnishness—either as part of the resolution of the narrated discrimination episode or within the evaluation of the episode. This is in line with previous discursive research, which has found that taking up a particular identity can allow a speaker to successfully make certain claims (e.g., Hansen, 2005; Jurva & Jasinskaja-Lahti, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In all accounts of discrimination presented in this subsection, speakers make relevant their own Finnishness in response to being excluded from Finnishness—either as part of the resolution of the narrated discrimination episode or within the evaluation of the episode. This is in line with previous discursive research, which has found that taking up a particular identity can allow a speaker to successfully make certain claims (e.g., Hansen, 2005; Jurva & Jasinskaja-Lahti, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Finnishness, thus, functioned as a discursive resource and a feature of both of the two strategies used when problematising discrimination. It is interesting to consider these findings in relation to Jurva and Jasinskaja-Lahti's (2015) study in the same ethnic remigration context, which highlighted how certain constructions of Finnishness could be used to explain one's "return" migration as highly desirable, as well as to work up a strong sense of natural belonging to Finnish society even before their move. Also in the current study, Finnishness was actively taken up and put to use either in the telling as part of the resolution to the discrimination episode or as part of the evaluation of the episode.…”
Section: Discussionmentioning
confidence: 99%
“…Williams and Husk, 2013;Driedger, 1976;Jenkins, 1994). This yields models of ethnicity that stress the fluid, the situational and the dynamic character of ethnic identification ( Jurva and Jasinskaja-Lahti, 2015;Neville et al, 2014;Nagel, 1994, p. 152). Ethnicity may change and it is not limited to State or national boundaries.…”
Section: Introductionmentioning
confidence: 97%
“…A recent strain of research has taken these concerns to heart ( Jurva and Jasinskaja-Lahti, 2015). Socio-cultural and interpretative methods have been employed to evaluate how evolving ethnic identities come about.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Norwegian classrooms, ethnic labels were “topicalized in situations of building and demonstrating alliances, of conflict and competition, and to escalate opposition when disputes had already surfaced” (Aukrust & Rydland, : 1538). Jurva and Jasinskaja‐Lahti () demonstrate how participants evoked ideas about being Finnish to account for a planned return migration to Finland, and Whitehead () shows how references to race in South African radio programmes served to add authority to praise. With this paper, I aim to deepen understanding of the interactional functions of ethnic labels.…”
Section: Labels and Categorization Among School Pupilsmentioning
confidence: 99%